2010
DOI: 10.1149/1.3430077
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Graphite in KF–AlF[sub 3]-Based Melt with Low Cryolite Ratio

Abstract: The electrochemical behavior of graphite in KF-AlF 3 -based melt with a cryolite ratio ͑molar ratio of KF to AlF 3 ͒ of 1.3 as well as a low oxygen content at 750°C was investigated by cyclic voltammetry, potentiostatic electrolysis, sampled-current voltammetry, and chronopotentiometry. Aluminum deposited on graphite at a potential of ca. 0.25 V ͑vs Al͒ and the electrochemical intercalation of potassium into graphite occurred at ca. Ϫ0.1 V ͑vs Al͒. The intercalation of potassium into graphite enhanced the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…Tao et al [29] came to the conclusion that the formation of Al 4 W in the NaF-KF-AlF 3 -Al 2 O 3 melts is predominantly controlled by mass transport while the deposition of aluminum is primarily controlled by charge transfer. The diffusion coefficient of Al(III) ions found in [26] was 1.77 × 10 −8 cm 2 •s −1 , which is rather low compared to the value 3.34 × 10 −6 •cm 2 •s −1 (even though the temperature was 110 • lower) obtained by Liu et al [30] who also stated that the aluminum reduction in the KF-AlF 3 melt is diffusion-controlled. Al 4 W alloy existed on the electrode surface and was tightly attached to the tungsten electrode surface after potentiostatic electrolysis.…”
Section: Introductioncontrasting
confidence: 53%
“…Tao et al [29] came to the conclusion that the formation of Al 4 W in the NaF-KF-AlF 3 -Al 2 O 3 melts is predominantly controlled by mass transport while the deposition of aluminum is primarily controlled by charge transfer. The diffusion coefficient of Al(III) ions found in [26] was 1.77 × 10 −8 cm 2 •s −1 , which is rather low compared to the value 3.34 × 10 −6 •cm 2 •s −1 (even though the temperature was 110 • lower) obtained by Liu et al [30] who also stated that the aluminum reduction in the KF-AlF 3 melt is diffusion-controlled. Al 4 W alloy existed on the electrode surface and was tightly attached to the tungsten electrode surface after potentiostatic electrolysis.…”
Section: Introductioncontrasting
confidence: 53%
“…These are close to the D values obtained for graphite and platinum electrodes in previous works. 21,22 The addition of the solid Al 2 O 3 and increases in its content in the KF-AlF 3 -Al 2 O 3(sat) suspensions lead to decreasing D values at the same temperature. sen due to the lower liquidus temperature 19,29 and larger limit current densities at the same other conditions.…”
Section: 3kf-alf 3 -Almentioning
confidence: 99%
“…[18][19][20] The results of the study supplement scarce data on the kinetics of aluminum electrowinning from KF-AlF 3 -Al 2 O 3 melts and suspensions. [21][22][23]…”
mentioning
confidence: 99%
“…Pure graphite’s failure in NIBs may have discouraged progress in using graphite as an electrode in K-ion batteries (KIBs). Electrochemical potassium insertion into graphite was conducted in molten KF or KF/AlF 3 at above 700 °C. , Wang et al reported reversible electrochemical insertion of potassium into nongraphitic carbon nanofibers at room temperature . In fact, KC 8 , the stage-one K-GIC, as the first discovered alkali metal GIC, has been readily synthesized by potassium vapor transport or by soaking graphite in a nonaqueous solution with potassium metal solvated. Surprisingly, it remains unknown whether K-GICs can be formed in an electrochemical K/graphite cell at room temperature.…”
mentioning
confidence: 99%